Booklet-based menstrual hygiene education and its effect on knowledge and attitudes of women - Harahap, Mustika Hana; Harahap , Afrida Sriyani; Harahap , Dewi Anggriani (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Menstrual hygiene is a crucial aspect of reproductive health, particularly for women of reproductive age (WRA) in correctional institutions where access to health education is often limited. Purpose: This study aimed to evaluate the effectiveness of booklet-based education in improving knowledge and attitudes of WRA regarding menstrual hygiene at the Women’s Correctional Facility in Pekanbaru City. Method: A quasi-experimental one-group pretest–posttest design was conducted involving 70 respondents selected through purposive sampling. Data were collected using validated questionnaires and analyzed with the Wilcoxon Signed-Rank Test. Results: Respondents’ knowledge increased from 68.6% to 95.7%, and positive attitudes from 71.4% to 95.7% after the intervention (p < 0.001). Conclusion: Booklet-based education significantly improved menstrual hygiene knowledge and attitudes among incarcerated women, supporting its use as a sustainable and scalable reproductive health education strategy in correctional facilities.